(untitled) (مجلة إحالات, 2026)
The folklore heritage plays a vital role in the cultural life of the nations and their history, since it reflects the nation’s identity throughout history. Therefore, this cultural diversity must be preserved by introducing it and discussing it in social media and mobile apps. This later has brought an artistic touch that preserves the nation’s heritage from being marginalized in comparison with the rapid growth and development of media and cultural globalization. As a result, this study attempts to shed light on some aspects of the folklore such as: " popular saying " and " folk joke " in the digital platforms.